Sociodemographic factors associated with Covid-19 in Canada - Mathew, Swapna Susan; Zain, Shadi (Nepal Mediciti Medical Journal, 2021)
BACKGROUND: Coronavirus disease or Covid-19 has caused more than 30 million documented infections and 1 million deaths worldwide as of Oct 2020. It was shown that several sociodemographic factors play a significant role in shaping the Covid-19 outcome and associated death rates across the globe. Thus the present study aims to study the sociodemographic parameters associated with the Covid-19 cases in Canada. MATERIAL AND METHODS: In this retrospective study, the data was collected from the Official data repository present in Canada. The patients’ data were evaluated and sociodemographic parameters were checked and recorded. After the data was recorded they are categorized based on the different states and statistical analysis was done. RESULT:The present study reported that in Canada total cases as reported in the repository are 1,253,519 cases. This result indicates that maximum of the patients suffering from Covid-19 belonged to the younger age category. Compared to the males, females were more to suffer from Covid-19. Most of the patients who required hospitalization were in the 80+ year age group (28.5%). Only 1.7% of patients in the age group below 19 years are required to be hospitalized. The regional data variation showed that in Alberta female patients were more in all the age groups compared with the male patients. Saskatchewan also reported a higher number of death cases in older people. In Manitoba, in the younger age category (0-29 years) less number of female patients suffered Covid-19. Interestingly, this number reversed as the age group increased. In Ontario, 72.1% of people reported being admitted to ICU and required a ventilator. In British Columbia, the gender distribution showed no such difference among all the Covid-19 positive cases. In Quebec among the covid-19 positive cases, 47.2% were male and 52.8% were females. CONCLUSION: Age is a significant predictor of Covid-19 mortality and patients from both genders aged more than 75 years and more need to provide more care and increased medical supervision to decrease the Covid-19 casualty.